Accelerated expansion of NATO into the Balkans as a consequence of Euro-Atlantic Discord - S. Gajić; E. G. Ponomareva (Vestnik MGIMO-Universiteta)
The Balkans in general and post-Yugoslav countries in particular have been under significant geopolitical pressure of the political West since the end of the bipolar global order. From the beginning of the Yugoslav Civil War in 1991, followed by Western recognition of secessionist republics in 1992 and NATO attacks on Serbs in Bosnia-Herzegovina in 1994-1995 and on the Federal Republic of Yugoslavia in 1999, the US, NATO and EU have been actively involved in the Balkan crisis. It was in concordance with the logic of unipolarity, or the New World Order, proclaimed by George W.H. Bush, in which there is “no substitute for American leadership”.The year of 2008 marked the start of profound changes. The changes we are witnessing today are of the magnitude described by Paul Kennedy’s classic The Rise and Fall of the Great Powers. Georgia’s attack on South Ossetia crossed Russia’s red lines and exposed the latter’s ambitions to regain the superpower status; China symbolically showed the same ambition with the Olympics in Beijing; the crash of the US real-estate market triggered the global economic crisis; and the NATO-sponsored unilateral declaration of secession by Kosovo Albanians set a precedent and introduced uncertainty in international law and the entire system of United Nations. By the beginning of 2020, many problems had accumulated in the EU – against the background of the ongoing migration crisis, right-wing and nationalist movements became more active, and differences between members increased. Long before COVID-19, Brexit became a serious stress test for the economy and social structure of the European Union. Dramatic changes took place on the other side of the Atlantic too, resulting in the shocking victory of staunch anti-globalist Donald Trump. The rules established during the 1991-2008 unipolarity have thus been challenged. Subsequently, post-Cold War ideological consensus in the West has also been challenged even further by the growth of non-systemic political movements – many of them directed not only against the EU expansion, but also against the EU itself.The significance of all these events for the Balkans is somewhat surprising and paradoxical, as the mainstream forces that have been weakened in the West forcefully push for a stronger Atlantic integration of the remaining Balkan countries. At the height of the pandemic, on 27 March 2020 Northern Macedonia became the 30th member of the Alliance, having previously undergone a humiliating procedure of changing its own name for this purpose. Three years earlier, Montenegro was admitted to NATO, but its population did not have the opportunity to vote on this in a referendum. The negotiations between Belgrade and Pristina on ‘normalisation of relations’, continued pressures on the prerogatives of Republic Srpska, Croatian initiative for a new Intermarium and many other similar efforts are stages in the process of NATOisation of former Yugoslavia. Based on the analysis of a large body of narrative sources and recent literature, the article presents the main trends and possible prospects for developments in the Balkans, depending on the outcome of the ongoing ideological and political struggle within the West.